2007
DOI: 10.1254/jphs.fp0070404
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of 5-Lipoxygenase Metabolite in Itch-Associated Response of Mosquito Allergy in Mice

Abstract: Abstract. This study investigated endogenous mediators involved in mosquito allergyassociated itching in mice. An intradermal injection of an extract of mosquito salivary gland elicited marked scratching in sensitized mice. The 5-lipoxygenase inhibitor zileuton (100 mg / kg), the 5-lipoxygenase activating peptide inhibitor MK-886 (10 mg / kg), and the glucocorticoid betamethasone 17-valerate (3 mg / kg) inhibited the scratching. The scratching was not affected by the cyclooxygenase inhibitors indomethacin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…However, the role of leukotrienes or prostaglandins in chronic dermatitis induced by repeated application of oxazolone is unclear so far. It has been reported that the 5-lipoxygenase inhibitor zileuton and the 5-lipoxygenase activating protein inhibitor MK-866 suppress itchassociated behavior induced by several pruritogens in mice (15,35,36). Furthermore, the oxazolone-induced severe scratching behavior was completely suppressed by pretreatment with zileuton, but not the cyclooxygenase inhibitor indomethacin or the platelet-activating factor-receptor antagonist YM264.…”
Section: Discussionmentioning
confidence: 98%
“…However, the role of leukotrienes or prostaglandins in chronic dermatitis induced by repeated application of oxazolone is unclear so far. It has been reported that the 5-lipoxygenase inhibitor zileuton and the 5-lipoxygenase activating protein inhibitor MK-866 suppress itchassociated behavior induced by several pruritogens in mice (15,35,36). Furthermore, the oxazolone-induced severe scratching behavior was completely suppressed by pretreatment with zileuton, but not the cyclooxygenase inhibitor indomethacin or the platelet-activating factor-receptor antagonist YM264.…”
Section: Discussionmentioning
confidence: 98%
“…In mice, cyproheptadine, a serotonin and histamine antagonist, inhibits the itch-related response to serotonin, but does not inhibit the response to mosquito allergy (5,6). Acute topical application of tacrolimus inhibits itch-related responses to mosquito allergy and proteinase-activated receptor-2 (PAR 2 ) agonist, but does not inhibit the responses to serotonin and histamine (7).…”
mentioning
confidence: 99%
“…Scratching induced by mosquito allergy is suppressed by a 5-lipoxygenase inhibitor and a 5-lipoxygenase activating peptide inhibitor, suggesting the involvement of 5-lipoxygenase metabolites in itch of mosquito allergy (15). Mosquito allergy-induced scratching is not inhibited by a leukotriene B 4 antagonist and cysteinyl leukotriene antagonists (15), but it is suppressed by an antagonist to lipoxin A 4 , a 5-lipoxygenase metabolite (30).…”
Section: Discussionmentioning
confidence: 99%
“…Mosquito allergy-induced scratching is not inhibited by a leukotriene B 4 antagonist and cysteinyl leukotriene antagonists (15), but it is suppressed by an antagonist to lipoxin A 4 , a 5-lipoxygenase metabolite (30). Although an intradermal injection of lipoxin A 4 does not elicit scratching in naive mice, it induces scratching in sensitized mice and also mice given adoptive transfer of CD4 + cells from the skin of sensitized ones (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation